The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/09638237.2016.1222061
|View full text |Cite
|
Sign up to set email alerts
|

Families and medication use and adherence among Latinos with schizophrenia

Abstract: Background Medication nonadherence among Latinos with schizophrenia represents a significant treatment obstacle. Although some studies have examined patient and family perceptions of adherence, few have examined these perceptions together. However, such knowledge can provide a deeper understanding of how family processes may contribute to or impede adherence among underserved groups such as Latinos. Aims This study explored perceptions of medication and adherence among Latinos with schizophrenia and key fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…In relation to this last point, as found by a recent study, it is likely that patients who struggled with medication had a difficult time acknowledging their illness. 18 On the other hand, several factors did not remained significant after adjustment such as country, monthly family income, more severe psychotic symptomatology, type of mental health treatment, and side effects.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In relation to this last point, as found by a recent study, it is likely that patients who struggled with medication had a difficult time acknowledging their illness. 18 On the other hand, several factors did not remained significant after adjustment such as country, monthly family income, more severe psychotic symptomatology, type of mental health treatment, and side effects.…”
Section: Discussionmentioning
confidence: 91%
“…The association between lack of insight and poor adherence has been extensively confirmed in previous studies. 11 , 18 , 58 62 This finding suggests that clinicians should enhance the detection of this problem of insight in Latin American countries and try to modify attitudes toward medication in SZ patients, especially by exploring and addressing concerns and patients’ distrust in pharmacotherapy. 59 Previous studies reported the importance of respecting and considering patients’ belief systems to improve medication attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Zou et al, 2014, p. 358) The Need for Guidance Because of difficulties in performing self-management tasks (see Table 3) independently, participants expressed the need for guidance (Aref-Adib et al, 2016;Chronister et al, 2015;Ouwehand et al, 2014). Participants stated difficulties in understanding and recalling information (Aref-Adib et al, 2016), thinking logically, making decisions (Fisher et al, 2017), being proactive (Doherty & MacGeorge, 2013;Fisher et al, 2017), making one's voice heard (Fisher et al, 2017;Topor et al, 2006), and expressing oneself (Aref-Adib et al, 2016;Hernandez & Barrio, 2017;Rusner et al, 2010). These difficulties were related to a lack of confidence, learning disabilities (Aref-Adib et al, 2016), unawareness of current symptoms (Chronister et al, 2015;Doherty & MacGeorge, 2013;Whitley & Campbell, 2014;Zou et al, 2013), a fear of what might happen (Ouwehand et al, 2014;Poremski et al, 2016;Rusner et al, 2010;Zou et al, 2013), or being overwhelmed (Aref-Adib et al, 2016;Chronister et al, 2015;Fisher et al, 2017;O'Connor et al, 2008;Ouwehand et al, 2014;Rusner et al, 2010).…”
Section: Table 4 (Continued)mentioning
confidence: 99%
“…10,11 Non-adherence is considered a complex phenomenon, which could be influenced by four factors: sociodemographic variables, psychotic symptomatology (including persecutory delusion, hostility, and cognitive impairment), variables related to treatment (frequency and intensity of side effects, subjective feeling under treatment, comorbid addiction, duration of treatment, and addictive behavior), and insight into the disorder. [12][13][14][15] Quality of life (QoL) is severely impaired in patients diagnosed with schizophrenia. 16 QoL and adherence to antipsychotics in patients have been studied extensively and independently.…”
Section: Introductionmentioning
confidence: 99%